Cellulose nanocrystals as non-innocent supports for the synthesis of ruthenium nanoparticles and their application to arene hydrogenation1. Issue 66 (19th July 2015) - Kaushik, Madhu; Friedman, Hava Meira; Bateman, Mary; Moores, Audrey
<x xml:space="preserve">Abstract</x> Ru nanoparticles deposited onto cellulose nanocrystals are highly active arene hydrogenation catalysts under mild conditions.